Can Neonatal Hypoglycemia be Considered a Risk Factor for Development of Acquired Arachnoid Cysts? - Vitali, Matteo; Cattalani, Andrea; Grasso, Vincenzo Maria; Longo, Gian Paolo; Sgubin, Donatella; Cremonte, Maurizio; Barbanera, Andrea (Journal of Pediatric Neurology, 2019)
Arachnoid cysts (ACs) are intra-arachnoid fluid collections and may be classified as primary or secondary in nature. Neonatal hypoglycemia (NH) is a common, life-threatening metabolic disorder in infants. We present the case of a term infant who suffered severe NH within 72 hours after birth and subsequently developed an acquired Sylvian AC.A child of 13 months of age, with history of severe NH within 72 hours after birth, was admitted after two generalized seizures. Magnetic resonance imaging (MRI) of the brain showed dimensional increase of a left Sylvian AC, not present on imaging on day one of life but revealed with a second MRI at 16 days of age. The timeline of events suggests some kind of correlation between the newborn's metabolic disorder, appearance of the AC, and its progressive expansion. We speculate that NH's organic consequences, i.e., cortical and white matter atrophy might have favored some kind of cerebral spinal fluid (CSF) dynamic alteration and AC development in our patient. Further structured studies are needed to confirm our hypothesis and reveal NH as a risk factor in the pathogenesis of ACs.
Keywords: arachnoid cyst; neonatal hypoglycemia; CSF collections; CSF dynamic; epilepsy; metabolic disorder